How do junior high school students solve proportional reasoning problems? - Filian Yunita Sari; Zulkardi; Ratu Ilma Indra Putri; Ely Susanti (Jurnal Elemen)
Proportional reasoning is a crucial skill that students need to master to achieve success in learning mathematics at both the elementary and secondary levels. This study aimed to identify the strategies junior high school students used when solving proportional reasoning problems related to ratios and proportions. This qualitative descriptive research was conducted on six seventh-grade students at a junior high school in Belitang, selected through purposive sampling. Data was collected using tests and interviews and analyzed descriptively. Data validity was ensured through triangulation techniques. The findings revealed that students with low abilities used a repeated addition strategy to solve proportional reasoning problems. Meanwhile, students with medium abilities employed the multiplication strategy but occasionally made errors using the additive strategy—students with high abilities predominantly used multiplicative strategies. The study suggests that students with medium abilities do not consistently apply proper proportional reasoning strategies, highlighting a need for further research into their solution approaches. In addition, it is essential to design learning activities that specifically target the improvement of proportional reasoning skills for students with lower abilities, given the critical role this skill plays in mathematics education at both the primary and secondary levels.